Diffusion phenomenon of lunar soil particles under a plume in a vacuum environment by numerical simulation. (June 2020) - Bo, Zhigang; Feng, Yulong; Huang, Wei; Cui, Yuhong
Abstract: During the landing of lunar probes on the surface of the Moon, lunar soil particles are lifted and diffused under the action of a plume. This study used three methods to numerically investigate the diffusion of lunar soil particles under a plume in a vacuum environment. First, an analytical solution of Fick's second law is used to obtain the motion results of lunar soil particles under the influence of diffusion in a steady state. Then, Fick's second law of finite-difference solution is used to obtain the motion results under the influence of diffusion. Finally, the discrete solution method of the mass- and energy-conservation equations is used to determine how the particles are affected by the plume in a transient state, including effects such as drag and lift, gravity, and temperature. The results show that lunar soil particles with small diameters diffuse more easily. After considering diffusion, the diffusion speeds of the 10- and 40-μm lunar soil particles are 3.6–4.5 times the speeds of those without diffusion; the spatial distribution range is increased by 1.4–4.5 times. The maximum lifting angle is increased by 1.0°–1.6°. However, lunar soil particles with diameters of 70 and 100 μm are not considerably affected by diffusion. At the same time, the introduction of the energy-loss coefficient showed that the impact of energy loss on the diffusion effect is substantial and that greater energy losses result in more diffusion-weakening trends. Compared with energy loss without considering the energy loss, diffusion speed is reduced by 10.2%–50.6%, occupied space is decreased by 18.3%–48.5%, and lifting angle is decreased by 18.8%–21.8%.Among the three methods, the mass- and energy-conservation method can fully consider the effects of particles and other factors. After considering the diffusion effect, the spatial distribution of lunar soil particles coheres better with the actual landing pictures, confirming that the impact of lunar soil particle diffusion on spatial distribution cannot be ignored. Highlights: Diffusion phenomenon of lunar soil particles under vacuum conditions is studied. Diffusion makes lunar soil particle distribution to cohere with landing pitture. Diffusion increases space of 10- and 40-μm lunar soil particle by 1.4–4.5 times. Considering the energy loss, space occupied by particles is reduced by 18.3%–48.5%.